Peran Pengadilan Niaga Dalam Menyelesaikan Eksekusi Putusan Pengadilan Hubungan Industrial - Heru Dwi Susanto; Joni Emirzon; Suci Flambonita (Qistie Jurnal Ilmu Hukum, 2025)
This study examines the role of the Commercial Court in executing decisions from the Industrial Relations Court (PHI), which often face technical and procedural obstacles despite having permanent legal force. The main barriers to the execution of PHI decisions are the low level of compliance by employers with the decisions and the high costs and lengthy time required for the execution process. The Commercial Court, with its more efficient procedures, can serve as an alternative to address these barriers, especially in cases involving companies facing financial difficulties. This research aims to analyze the legal construction of executing PHI decisions through the Commercial Court and provide recommendations for improving the existing legal system. The research method used is normative legal research with approaches based on legislation, case law, and historical analysis, which leads to the conclusion that the use of the Commercial Court can improve execution efficiency and provide legal certainty. It is recommended that there be stronger synergy between industrial relations law and commercial law, as well as regulatory updates to support the implementation of fairer and more efficient executions.